Die ausgefallene Disputation über den Ablass im Rahmen des Wittenberger Disputationswesens - Leppin, Volker (Catholica <Münster>, 2024)
The essay alms to put the would-have-been disputation about Luther's 95 theses into a broader context. The first step elaborates on the genre of disputation at medieval universities in general. In the second step, the Wittenberg ordinances are presented. Then, the author looks at how Luther's understanding of indulgence was handled at Wittenberg academic circles around 1517. The essay ends with an outlook on the transformation of the genre of disputation from deliberating to publicly demonstrating claimed truth.